PENGEMBANGAN MEDIA PEMBELAJARAN IPS BERBASIS PERMAINAN MONOPOLI - Islamiyah, Tsuaibatul (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2017)
Some students still consider IPS as a boring subject. It is because almost all material contains descriptive so encourages the teacher used a lecture method. Many students felt sleepy when the learning occurred. Monopoly as one of the fun games could be modified into social instructional media. So that students could be more active and enthusiastic about learning. The aim of this research is: (1) Produce teaching materials in instructional media form; (2) Know the validity of instructional media; (3) Know the ratio of control class and experiment class result. The method that is used in this research is the Research and Development (RD) method, to create teaching material. The subject of product assessment for the worthiness of this instructional media is divided by 3 experts: content expert, media expert, and learning expert. The target of product trial are the students of grade 8 Islamic Junior High School Student Nurul Ulum Malang. The result of this research is produced 3D product resemble a monopoly game. The difference is these learning media have material of Indonesia Freedom preparations theme. The result of this development research in the form of monopoly game has the level of eligibility by containing expert validity is 95%, media expert validity is 80%, and learning expert validity is 75%. The average of control class post-test result is 72.5, and experiment class post-test result is 79.1. On gain, score tries out knew that control class was increasing 14.3%, while experiment class was 19.7%. it can be concluded that learning outcome of the class using instructional media based on social science monopoly game is more increasing than a class which is not using instructional media based on social science monopoly.Keywords: instructional media, monopoly game, social science